IN TEACHING TECHNOLOGY TEACHER'S CREATIVE APPROACH - Shomirzaev Maxmatmurod Xuramovich (Scholar Express Journal, 2022)
The article discusses some aspects of the organization of new pedagogical technologies in the teaching of technology in general secondary schools, including the effectiveness of the use of interactive methods in the teaching of technology
Keywords: Technology; Student; Teaching; Technological Process